Experimental approaches for modeling and targeting resistant neuroblastoma - Seger, Alexandra ; 0000-0003-3191-5302 (Lund University, Faculty of Medicine Doctoral Dissertation Series, 2025)
High-risk neuroblastoma (NB) is a rare, solid childhood cancer with poor prognosis due to treatment resistance and metastasis. Improved patient outcome is dependent on the understanding of the resistance mechanisms and subsequent development of novel treatment options. In Paper I, we established a clinically relevant in vivo treatment protocol using current standard-of-care chemotherapy (COJEC). We observed higher genetic diversity in intrinsically resistant NB, mesenchymal-like (MES) phenotype in NB with acquired resistance and an ADRN phenotype in treatment responsive NB. Tumor organoids derived from these treated and resistant NBs retained their phenotype and chemotherapy resistance in vitro. In Paper II we focused on targeting ferroptosis, a therapeutic vulnerability in NB due to upregulation of antioxidant pathways. We highlighted the importance of carefully selecting the mechanisms of action for ferroptosis induction as treatments targeting GPX4 interfered with COJEC. Treatment combinations with COJEC and thioredoxin reductase inhibitor auranofin resulted in reduction of cells with the resistant MES-like phenotype. In Paper III we investigated TRPA1 as potential treatment target due to its expression in relapsed NB. Inhibition of TRPA1 reduced viability of NB in vitro, but not in vivo. Pre-treatment using TRPA1 inhibitors resulted in additive or even synergistic effects with COJEC. In Paper IV we established a novel humanized in vivo model using small human derived bones (hOss) and different injection methods to successfully simulate the different stages of the metastatic process. COJEC treatment reduced metastasis and resulted in minimal residual disease (MRD). Overall, we established a clinically relevant in vivo chemotherapy protocol to investigate treatment resistant and relapsed neuroblastoma. By establishing a humanized in vivo model of metastatic neuroblastoma, we provided a platform to investigate metastasis treatment resistance and MRD. Uncovering sensitivities of resistant or relapsed NB, we investigated ferroptosis induction and TRPA1-inhibition and their combability to COJEC.
Keywords: Cancer; Neuroblastoma; Preclinical; Treatment; Metastasis